2016
DOI: 10.1002/bin.1455
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Within‐Trial Treatment Integrity of Discrete‐Trial Teaching Programs Using Sequential Analysis

Abstract: Discrete-trial teaching is a strategy frequently used to teach functional skills to individuals with developmental and intellectual disabilities. Research has shown that the within-trial components of the procedure should be administered with ≥90% treatment integrity to facilitate optimal learning. Usually within-trial treatment integrity is measured using whole-session methods such as percentage of trials correctly administered. This study demonstrated one-step Markov transition matrices as a method of assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 17 publications
1
11
0
Order By: Relevance
“…Following initial training, treatment integrity checks need to be conducted periodically to detect any procedural inaccuracies (e.g., Brand et al, 2017) or instances of treatment drift (e.g., Hansford et al, 2010) so that interventionists can quickly be retrained to conduct procedures consistent with their prescribed protocols. The staff training literature contains several examples of indirect (e.g., permanent product; e.g., Noell et al, 2005) and direct methods (e.g., checklists, data sheets; e.g., Clayton & Headley, 2019) that can be used to conduct quick treatment integrity spot checks (e.g., DiGennaro Reed et al, 2018;McIntyre et al, 2007) throughout the course of treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following initial training, treatment integrity checks need to be conducted periodically to detect any procedural inaccuracies (e.g., Brand et al, 2017) or instances of treatment drift (e.g., Hansford et al, 2010) so that interventionists can quickly be retrained to conduct procedures consistent with their prescribed protocols. The staff training literature contains several examples of indirect (e.g., permanent product; e.g., Noell et al, 2005) and direct methods (e.g., checklists, data sheets; e.g., Clayton & Headley, 2019) that can be used to conduct quick treatment integrity spot checks (e.g., DiGennaro Reed et al, 2018;McIntyre et al, 2007) throughout the course of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Research is needed to assess the extent to which these features affect the risk of treatment inaccuracies. For example, descriptive studies (e.g., Brand et al, 2017Carroll et al, 2013;Cook et al, 2015) can be conducted to assess the frequency and likelihood of treatment inaccuracies when implementing procedures of varying complexity (McIntyre et al, 2007). Additionally, monitoring and reporting treatment integrity were treated as equivalent when coding studies for risk.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the integrity checkers or raters were designated to ensure that the therapists followed the guidelines and steps embedded in the treatment manual. The checkers were developed to evaluate two major dimensions of treatment integrity which include adherence to the coaching manual, and the coaches competence 44 The adherence to REOHC manual dimension was checked using an adapted form of the Cognitive Behavioural Therapy-Adherence Scale (CBT-AS) used in earlier studies [44][45][46] The adapted checker is named which was named REOHC Adherence and is measured on a 3-point scale of not adherent = 0; partly adherent = 1, and adherent = 2. Scale and showed inter-rater high reliability (IRR = .72).…”
Section: Treatment Integritymentioning
confidence: 99%
“…Future applied research could involve conducting direct observations of procedures administered for tasks that have already been mastered in the natural environment and documenting the types of errors that are likely to occur during this phase of learning (e.g., Brand et al, 2017; Brand et al, 2018; Breeman et al, 2020; Carroll et al, 2013; Cook et al, 2015; Donnelly & Karsten, 2017; Foreman et al, 2020; Kodak et al, 2018). Documenting these naturalistic error types will allow researchers to investigate how commonly occurring errors affect learning postmastery (i.e., increasing the ecological validity of the research; Brand et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Descriptive studies have found that procedural errors occur readily in applied settings (e.g., Brand et al, 2017, 2018; Breeman et al, 2020; Carroll et al, 2013; Cook et al, 2015; Donnelly & Karsten, 2017; Foreman et al, 2020; Kodak et al, 2018). These studies also indicate that those implementing behavioral interventions are likely to make errors when administering consequences following learners' target responses.…”
mentioning
confidence: 99%